The Effect of Exercise on the Blood Pressure and Heart Rate in Obese and Patient with Hypertension: Case-Control-Study - Huda Jabbar Dibby (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Obesity is considered in daily clinical practice as one of the main health problems widelydistributed over the world and it signifies a actual task to both community and individual health (1-3).Furthermore, hypertension is main cause of ( ischemic heart disease) and cerebrovascular accidents.it hasbeen improved in literatures which established on long term follow up the importance of regular exercise fortreatment of obesity and hypertension though short term complications have established little consideration.Aim of Study: to assess the effect of exercise on hemodynamic response in a patient sample with hypertensionand hypertensive obese patients.Patients and Methods: A Selected patients from those visiting the outpatient of medicine at AL-DiwaniyahTeaching Hospital and who suffer from primary hypertension and randomly distributed to two groups: obesehypertensive and hypertensive without obesity . A third group who are non-hypertensive obesity patientsalso randomly select from a group of patients who are visiting outpatient of medicine for viral diseases acuteself-limiting illness. A control group of seemingly healthy individuals involved doctors in the hospital anda health staff.Results: a highly significant of the mean systolic blood pressure of patient with hypertension and obesehypertensive patients than of both the obese and control “groups [p< 0.05]. A highly significant meandiastolic-blood pressure of patient with hypertension and obese hypertensive-patients than that of both theobese and control groups [P < 0.05], highly significant mean-heart/rate of patients with hypertension andobese patients with hypertension than that of both obese and control groups [P < 0.05]”. Also, after extremeworkout and 15 min. following rest there was significantly different in hemo-dynamic reaction after extremeworkout and 15 minutes following rest between groups.Conclusion: After extreme workout and 15 minutes after rest a significant difference was found among thegroups.